Osmotic Demyelination Syndrome following Correction of Hyponatremia by ≤10 mEq/L per Day. Issue 9 (30th September 2021) - Tandukar, Srijan; Sterns, Richard H.; Rondon-Berrios, Helbert
Visual Abstract: Abstract : Key Points: Osmotic demyelination syndrome (ODS) can occur despite adherence to current hyponatremia correction guidelines, especially in patients with serum sodium <115 mEq/L. Limit the rate of correction of serum sodium <8 mEq/L in any 24-hour period in these patients to minimize the risk of ODS. Thiamine supplementation should be considered for any patient with hyponatremia whose dietary intake has been poor. Background: Overly rapid correction of chronic hyponatremia may lead to osmotic demyelination syndrome. European guidelines recommend a correction to ≤10 mEq/L in 24 hours to prevent this complication. However, osmotic demyelination syndrome may occur despite adherence to these guidelines. Methods: We searched the literature for reports of osmotic demyelination syndrome with rates of correction of hyponatremia ≤10 mEq/L in 24 hours. The reports were reviewed to identify specific risk factors for this complication. Results: We identified 19 publications with a total of 21 patients that were included in our analysis. The mean age was 52 years, of which 67% were male. All of the patients had community-acquired chronic hyponatremia. Twelve patients had an initial serum sodium <115 mEq/L, of which seven had an initial serum sodium ≤105 mEq/L. Other risk factors identified included alcohol use disorder ( n =11), hypokalemia ( n =5), liver disease ( n =6), and malnutrition ( n =11). The maximum rate of correction in patients with serum sodium <115 mEq/L was at least 8 mEq/L in all but one patient. In contrast, correction was <8 mEq/L in all but two patients with serum sodium ≥115 mEq/L. Among the latter group, osmotic demyelination syndrome developed before hospital admission or was unrelated to hyponatremia overcorrection. Four patients died (19%), five had full recovery (24%), and nine (42%) had varying degrees of residual neurologic deficits. Conclusion: Osmotic demyelination syndrome can occur in patients with chronic hyponatremia with a serum sodium <115 mEq/L, despite rates of serum sodium correction ≤10 mEq/L in 24 hours. In patients with severe hyponatremia and high-risk features, especially those with serum sodium <115 mEq/L, we recommend limiting serum sodium correction to <8 mEq/L. Thiamine supplementation is advisable for any patient with hyponatremia whose dietary intake has been poor.